Predictors of Graduates’ Performance in the Licensure Examination for Teachers (LET) - Dionio, Beverly B.; Dagpin, Aubrey Rachel R.; Cabillas, Alecjia Jean Quel B.; Edullantes, Jocie Rose T.; Baluyos, Genelyn R. (EduLine: Journal of Education and Learning Innovation, 2025)
Passing the Licensure Examination for Teachers (LET) demands thorough preparation due to its complexity. This study aimed to identify predictors of LET performance among College of Education graduates. Using a descriptive-correlational design, the researchers analyzed graduates' profiles, academic records, On-the-Job Training scores, and LET results through documentary analysis. Thirty-seven graduates were selected through purposive sampling. Statistical methods included mean, standard deviation, frequency, Percentage, Pearson correlation, and stepwise multiple regression analysis. The study found that graduates' school performance, particularly in teaching competencies, special demonstrations, internships, and General Weighted Average (GWA), was very good. LET performance was also strong in general education, professional education, and major subjects. Significant relationships were identified between LET performance and factors such as special demonstrations, internships, and GWA while teaching competencies had a less consistent impact. The study concluded that school performance, especially GWA, was a significant predictor of LET success in general education, major subjects, and overall performance. Enhancing pre-service academic performance through curriculum improvements, hands-on activities, and targeted support can boost LET outcomes.